2020
DOI: 10.1017/s1359135520000275
|View full text |Cite
|
Sign up to set email alerts
|

Briefing a children’s hospice: bridging the evidence gap and redefining value in contemporary healthcare design

Abstract: Knowledge produced within the field of evidence-based design seeks credible data to support decision-making in the architectural design process. When directed towards the design of healthcare settings, such knowledge can support both the optimisation of patient healing and the improvement of staff performance in ways that correlate positively with patient safety and well-being. Spatial configurations that improve co-worker proximity, visibility, and communication can have a positive influence on staff percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Where staff perceived the environment to impede the possibility of healing, and particularly where the environment was seen to unnecessarily exacerbate patient and family distress, staff also found this distressing. Other studies have similarly observed that where the ability of staff to deliver an appropriate level of patient care is compromised by external and competing factors, both including and beyond those related to the built environment, this results in feelings of frustration (Bartlett & Clarke, 2012;McLaughlan & Pert, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Where staff perceived the environment to impede the possibility of healing, and particularly where the environment was seen to unnecessarily exacerbate patient and family distress, staff also found this distressing. Other studies have similarly observed that where the ability of staff to deliver an appropriate level of patient care is compromised by external and competing factors, both including and beyond those related to the built environment, this results in feelings of frustration (Bartlett & Clarke, 2012;McLaughlan & Pert, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…That staff expressed such awareness, and indeed concern, for patient and family well-being suggests that improving the built environment for the benefit of patient and family comfort might also positively impact staff well-being (also see McLaughlan & Pert, 2020). It would be remiss of us, however, to make this observation without also acknowledging that this could compound an existing risk; the needs of palliative care staff could be easily overlooked within architectural briefing processes because staff are likely to prioritize the needs of patients and families above their own.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations